Coverage-driven dissociation of azobenzene on Cu(111): a route towards defined surface functionalization. Issue 83 (4th September 2015) - Willenbockel, Martin; Maurer, Reinhard J.; Bronner, Christopher; Schulze, Michael; Stadtmüller, Benjamin; Soubatch, Serguei; Tegeder, Petra; Reuter, Karsten; Stefan Tautz, F.
Abstract : Adsorption on Cu(111) induces catalyzed dissociation of azobenzene resulting in highly structured phenyl nitrene monolayer. Abstract : We investigate the surface-catalyzed dissociation of the archetypal molecular switch azobenzene on the Cu(111) surface. Based on X-ray photoelectron spectroscopy, normal incidence X-ray standing waves and density functional theory calculations a detailed picture of the coverage-induced formation of phenyl nitrene from azobenzene is presented. Furthermore, a comparison to the azobenzene/Ag(111) interface provides insight into the driving force behind the dissociation on Cu(111). The quantitative decay of azobenzene paves the way for the creation of a defect free, covalently bonded monolayer. Our work suggests a route of surface functionalization via suitable azobenzene derivatives and the on surface synthesis concept, allowing for the creation of complex immobilized molecular systems.